Osgood–Schlatter disease: a 2020 update of a common knee condition in children. Issue 1 (February 2020) - Ladenhauf, Hannah N.; Seitlinger, Gerd; Green, Daniel W.
Abstract : Purpose of review: Osgood–Schlatter disease (OSD) is one of the most common causes for anterior knee pain in children and adolescents resulting from a traction apophysitis of the tibial tubercle. While a peak in boys aged 12–15 years old was well documented, there seems to be no difference in sex distribution nowadays. This may result from increased participation of young females in high-impact sports. This review provides an up-to-date account on contemporary prophylaxis as well as diagnostic and therapeutic approaches. Recent findings: Numerous studies have examined risk factors for OSD. These include body weight, muscle tightness, muscle weakness during knee extension and flexibility of hamstring muscles. In particular, shortening of the rectus femoris may substantially alter biomechanical functions of the knee. Conservative management remains successful in over 90% of patients. However, if disabling symptoms and pain persistent after physeal closure, operative treatment may be necessary. Summary: OSD is a mostly self-limiting apophysitis of the tibial tubercle and the adjacent patella tendon in young active patients with open physis. Prevention strategies include quadriceps and hamstring stretching and therefore should be implemented in everyday practice routines for children who partake in regular sports activities.